2001
DOI: 10.1038/sj.bjp.0703843
|View full text |Cite
|
Sign up to set email alerts
|

Two subtypes of G protein‐coupled nucleotide receptors, P2Y1 and P2Y2 are involved in calcium signalling in glioma C6 cells

Abstract: ] i . 6 ADP inhibited isoproterenol-induced cyclic AMP accumulation. PTX blocked this eect, but PPADS did not. 7 RT ± PCR analysis revealed the molecular identity of P2Y receptors expressed by glioma C6 cells to be both P2Y 1 and P2Y 2 . 8 It is concluded that both P2Y 1 and P2Y 2 receptors co-exist in glioma C6 cells. ADP acts as agonist of the ®rst, and ATP and UTP of the second one. Both receptors are linked to phospholipase C (PLC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…In the presence of EGTA, UTP caused a transient increase in [Ca 2+ ] i to 2.38± AU; following the return to the baseline the addition of CaCl 2 led to an increase of [Ca 2+ ] i to 1.83±0.11 AU (n=97). The same kinetics of the biphasic Ca 2+ response induced by 100 μM ATP or 10 μM ADP in glioma C6 cells was shown previously [14,15,20]. Thus, BzATP, similar to ATP, UTP, and ADP, generates the depletion of the ER stores that gives a signal to voltage-independent Ca 2+ channels and gives rise to Ca 2+ influx across plasma membrane.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…In the presence of EGTA, UTP caused a transient increase in [Ca 2+ ] i to 2.38± AU; following the return to the baseline the addition of CaCl 2 led to an increase of [Ca 2+ ] i to 1.83±0.11 AU (n=97). The same kinetics of the biphasic Ca 2+ response induced by 100 μM ATP or 10 μM ADP in glioma C6 cells was shown previously [14,15,20]. Thus, BzATP, similar to ATP, UTP, and ADP, generates the depletion of the ER stores that gives a signal to voltage-independent Ca 2+ channels and gives rise to Ca 2+ influx across plasma membrane.…”
Section: Resultsmentioning
confidence: 56%
“…The biphasic process that involves PLC stimulation and inositol-1,4,5-trisphosphate (IP 3 ) formation causes release of Ca 2+ from the ER store via IP 3 receptors (the first phase of the response) and is followed by capacitative Ca 2+ entry via voltage-independent Ca 2+ channels in the plasma membrane, as a consequence of the depletion of the ER store (the second phase of the response) [6,7]. Such process is ubiquitous in all nonexcitable cells and has been previously described by us in glioma C6 as the result of ATP and UTP-evoked P2Y 2 receptor activation [8,14,15,20]. Similarly, we have demonstrated that in C6 cells, thapsigargin, acting without IP 3 production as a specific inhibitor of the ER Ca 2+ -ATPase, initiated Ca 2+ response consistent with the capacitative model of Ca 2+ entry, in which the depletion of intracellular stores provides a signal for the transmembrane Ca 2+ influx [8,20].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Given that extracellular ATP can bind to P 2 X 7 cationic channel (27) and P 2 Y 1 /P 2 Y 2 G-protein coupled (28) purinergic receptors, both shown to be expressed in C6 glioma cells (29,30), we then determined which receptor pathway is dominant in aggregate compaction. Wild-type and Panx1 rods were first treated with suramin (100 M), a nonspecific purinergic antagonist.…”
Section: Panx1-mediated Atp Release Drives Compaction Via a Signal Camentioning
confidence: 99%